2019
DOI: 10.1186/s12913-019-4570-7
|View full text |Cite
|
Sign up to set email alerts
|

Are perceived bad working conditions and perceived workplace bullying associated with doctor visits? Results of the nationally representative German General Social Survey

Abstract: Background The reason for doctor visits associated with bad working conditions (and workplace bullying) remains unknown. Therefore, the aim of this study was to examine the association between perceived working conditions as well as workplace bullying and the number of doctor visits as well as the reason for seeing a doctor. Methods Data were derived from the German General Social Survey, a representative cross-section of the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Subsequently, multiple negative binomial regressions (with robust standard errors) were used to examine the association between post-materialism and the frequency of doctor visits in the past three months (total sample and stratified by sex). Additionally, the association between post-materialism and the reason for doctor visits (outcome measures: reason for doctor visits: acute illness; chronic illness; felt unwell; requesting advice; visit to the doctor's office, but without consulting the doctor; preventive medical check-up/vaccination) was examined using multiple logistic regressions (stratified by sex) [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, multiple negative binomial regressions (with robust standard errors) were used to examine the association between post-materialism and the frequency of doctor visits in the past three months (total sample and stratified by sex). Additionally, the association between post-materialism and the reason for doctor visits (outcome measures: reason for doctor visits: acute illness; chronic illness; felt unwell; requesting advice; visit to the doctor's office, but without consulting the doctor; preventive medical check-up/vaccination) was examined using multiple logistic regressions (stratified by sex) [20].…”
Section: Discussionmentioning
confidence: 99%
“…Drawing on Andersen's behavioral model [2], covariates were chosen [20]. Predisposing characteristics were included as follows: sex, age, family status (0 = married and living apart; widowed; divorced; never married; civil partnership, living apart; registered partner deceased; civil partnership dissolved; 1 = married and living together with spouse; civil partnership, living together), education (ISCED-97 [21]): basic education, lower secondary, upper secondary, post-secondary, higher tertiary, and upper tertiary).…”
Section: Covariatesmentioning
confidence: 99%
“…is the author/funder, who has granted medRxiv a license to display the preprint in (which was not certified by peer review) study reported that workplace bullying was associated with increased doctor visits, the diagnosis is unknown (13). On the other hand, several qualitative studies have reported that victims of workplace bullying had symptoms of asthma or gastric ulcers (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…There is a considerable amount of articles showing that the working environment influences health (Hajek & König, 2019). Some focus more particularly on the effect of earnings (Kronenberg et al., 2017; Reeves et al., 2017), working time (Berniell & Bietenbeck, 2020; Cygan‐Rehm & Wunder, 2018; Lepinteur, 2019; Sánchez, 2017), occupations (Cutler et al., 2008; Mackenbach et al., 2003; Ravesteijn et al., 2018) or occupational health hazard (Karnon et al., 2005; Olsen, 2012; Pouliakas & Theodossiou, 2013).…”
Section: Introductionmentioning
confidence: 99%